Adhesive composition, adhesive cured product, joined body, method for manufacturing joined body, and bonding method
The adhesive composition, using epoxy resin, anhydride curing agents, and ester exchange catalysts, addresses the need for strong, durable, and easily dismantlable adhesives by leveraging vitrimer properties for thermal responsiveness and recyclability.
Patent Information
- Application Number
- JP2024115991
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-20
- Filing Date
- 2024-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
Existing adhesives do not meet the demands for high adhesive strength, durability, impact resistance, and ease of dismantling and reconnection, particularly in applications requiring thermal response and recyclability.
An adhesive composition incorporating epoxy resin, anhydride-based curing agents, ester exchange catalysts, and polymers with ester exchange groups, utilizing vitrimer properties to enable reversible topology changes for easy dismantling and reconnection, while maintaining strong adhesive characteristics.
The adhesive composition exhibits excellent adhesive strength, thermal responsiveness, and ease of dismantling and reconnection, allowing for efficient recycling and repair of bonded materials.
Smart Images

Figure 2025015520000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition, a cured adhesive, a bonded body, a method for producing a bonded body, and a bonding method. [Background technology]
[0002] Adhesives made of curable resins such as thermosetting resins and photocurable resins are cured by external stimuli such as heat and light, and do not require special devices or methods for curing. Therefore, curable resins are widely used for adhesion applications. On the other hand, in the field of adhesives, various properties such as durability, impact resistance, vibration resistance, and thermal stress relief are required, as well as adhesive strength. In recent years, in order to easily dismantle a bonded body bonded with an adhesive, the properties required of adhesives have been expanding, such as easy dismantling, which is a property in which the adhesive strength decreases under certain conditions, and re-adhesion, which is a property in which the adherends are re-adhered after being dismantled.
[0003] In order to meet such required characteristics, it has been proposed to use the properties of a compound called "vitrimer", whose topology changes reversibly when stimulated by heat or light, in an adhesive. Although vitrimer is a crosslinked resin, it has fluidity only under certain conditions and can flow like a viscoelastic liquid. Therefore, by utilizing the properties of vitrimer, it is possible to impart various functions to the adhesive. For example, Non-Patent Document 1 describes an epoxy adhesive that uses aromatic disulfide bonds. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Hsing-Ying Tsai et al., "Strengthening epoxy adhesives at elevated temperatures based on dynamic disulfide bonds," Materials Advances, Vol. 1 (2020), pp. 3182-3188 Summary of the Invention [Problem to be solved by the invention]
[0005] However, an adhesive having even better performance than the epoxy adhesive of Non-Patent Document 1 is desired.
[0006] The present invention has been made in view of the above background, and aims to provide an adhesive composition which improves adhesive properties such as adhesive strength and which has functions such as easy dismantling and re-adhesion, a cured adhesive product obtained by curing this adhesive composition, a bonded body, a method for producing a bonded body, and an adhesion method. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the present inventors discovered that by imparting vitrimer properties to a cured product of an adhesive composition containing an epoxy resin and an acid anhydride curing agent using a specific catalyst and additive, it is possible to improve the adhesive properties of the adhesive composition and impart various functions to the adhesive composition, thereby completing the present invention.
[0008] [1] An epoxy resin (A), An acid anhydride curing agent (B); A transesterification catalyst (C); and (D) a polymer having an ester exchangeable group. [2] The adhesive composition according to [1], wherein the adhesive composition contains polycaprolactone (D1) as the polymer (D). [3] The adhesive composition according to [1], wherein the adhesive composition comprises a polyrotaxane (D2) as the polymer (D), the polyrotaxane (D2) having a cyclic molecule having a side chain including an ester group, and a linear molecule that is included in a ring of the cyclic molecule and has capping groups at both ends. [4] The adhesive composition according to [3], wherein a side chain of the cyclic molecule contains a structural unit derived from polycaprolactone.
[0009] [5] The adhesive composition according to any one of [1] to [4], having adhesive properties such that a test piece obtained by bonding an adherend made of aluminum using the adhesive composition has a tensile shear adhesive strength of 20 MPa or more at 25°C. [6] The adhesive composition according to any one of [1] to [5], having adhesive properties such that the tensile shear adhesion strength of the adhesive composition at 200°C is less than 10% of the tensile shear adhesion strength of the adhesive composition at 25°C. [7] The adhesive composition according to any one of [1] to [6], wherein a tensile shear bond strength test is conducted on a test piece obtained by bonding an adherend made of aluminum with the adhesive composition, and the test piece is broken to obtain two adherends which are then re-bonded via a cured product of the adhesive composition, and the adhesive composition has adhesive properties such that the tensile shear bond strength at 25°C is 12 MPa or more.
[0010] [8] A cured adhesive product obtained by curing the adhesive composition according to any one of [1] to [7]. [9] A first member; A second member; and a cured adhesive material interposed between the first member and the second member, A bonded body, wherein the adhesive cured product is the adhesive cured product described in [8].
[0011]
[10] A method for producing a bonded body including a first member, a second member, and an adhesive cured product interposed between the first member and the second member, comprising the steps of: A method for producing a bonded body, the method comprising interposing the adhesive composition according to any one of [1] to [7] between the first member and the second member, and curing the adhesive composition in a state where the adhesive composition is interposed.
[11] A bonding method for bonding a first member and a second member using the adhesive composition according to any one of [1] to [7], contacting the first member and the second member with the adhesive composition; and and promoting a transesterification reaction between the epoxy resin (A) and the polymer (D). Effect of the Invention
[0012] The adhesive composition of the above embodiment has excellent adhesive properties such as excellent adhesive strength, ease of thermal stress relaxation, excellent durability, etc. In addition, the adhesive composition of the above embodiment has functions such as easy dismantling property and re-adhesion property.
[0013] Therefore, according to the above-described aspects, it is possible to provide an adhesive composition which improves adhesive properties such as adhesive strength and which has functions such as easy dismantling and re-adhesion, an adhesive cured product obtained by curing this adhesive composition, a bonded body, a method for producing a bonded body, and an adhesion method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The following describes in detail an embodiment of the present invention. The description of the components described below is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to the following content as long as it does not exceed the gist of the present invention.
[0015] (Adhesive Composition) The adhesive composition contains at least an epoxy resin (A), an acid anhydride curing agent (B), and an ester exchange catalyst (C). The adhesive composition further contains a polymer (D) having an ester exchangeable group. The adhesive composition contains the ester exchange catalyst (C) and the polymer (D) having an ester exchangeable group in addition to the epoxy resin (A) and the acid anhydride curing agent (B), and thus the cured product of the adhesive composition can be imparted with vitrimer properties. The adhesive composition having such a composition can be used, for example, as an adhesive.
[0016] Here, the term "vitrimer" refers to a compound whose topology changes reversibly in response to a stimulus of heat or light. For example, a bond exchange reaction is utilized for the change in topology in a vitrimer. For example, a vitrimer whose topology changes due to heat has a sufficiently slow reaction rate of the bond exchange reaction at a relatively low temperature and behaves as a solid. On the other hand, when the temperature of the vitrimer exceeds a temperature called the vitrimer transition temperature (Tv), the reaction rate of the bond exchange reaction increases rapidly, and the vitrimer becomes able to flow like a viscoelastic liquid. Therefore, for example, by imparting the properties of a vitrimer to an adhesive made of a thermosetting adhesive composition, it becomes possible to impart various functions to the adhesive.
[0017] In the adhesive composition, transesterification is used to impart vitrimer properties to the cured product of the adhesive composition. That is, the cured product obtained by curing the epoxy resin (A) with the acid anhydride curing agent (B) contains ester groups. In addition, since the polymer (D) added to the adhesive composition contains groups capable of transesterification, some of the groups capable of transesterification in the polymer (D) are bonded to hydroxyl groups formed by ring-opening of the epoxy groups of the epoxy resin (A) by the transesterification reaction, or ester groups and carboxy groups formed by ring-opening of the acid anhydride groups of the acid anhydride curing agent (B).
[0018] Therefore, the cured product of the adhesive composition has a structure in which the polymer (D) is efficiently incorporated into the crosslinked structure of the epoxy resin (A) at a temperature lower than the vitrimer transition temperature. In this manner, the incorporation of the polymer (D) into the crosslinked structure of the epoxy resin (A) can improve the mechanical properties and adhesive strength of the adhesive.
[0019] On the other hand, the adhesive composition further contains an ester exchange catalyst (C). The ester exchange catalyst (C) can significantly increase the reaction rate of the ester exchange reaction under desired conditions and impart the properties of a vitrimer to the cured product. Therefore, by heating a bonded body prepared using the adhesive composition to the vicinity of the vitrimer transition temperature, the adhesive strength of the adhesive composition can be significantly reduced. As a result, one of the bonded bodies constituting the bonded body can be easily separated from the other bonded body, and the bonded body can be disassembled. Furthermore, by bonding the bonded bodies separated in this way via the cured product of the adhesive composition while heating them to a temperature near or higher than the vitrimer transition temperature, it becomes possible to bond the bonded bodies again. In this way, the adhesive composition has easy dismantling and re-adhesion properties.
[0020] [Epoxy resin (A)] As the epoxy resin (A) contained in the adhesive composition, for example, an epoxy resin used in an epoxy adhesive can be used. More specifically, as the epoxy resin (A) contained in the adhesive composition, for example, glycidyl ether type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, biphenyl type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, tetrabromobisphenol A type epoxy resin, and other polyfunctional phenol type epoxy resins; epoxy resins obtained by hydrogenating the aromatic ring of an aromatic epoxy resin; glycidyl ester type epoxy resin; glycidyl amine type epoxy resin; alicyclic epoxy resin; and heterocyclic epoxy resin. Among these, the epoxy resin (A) is preferably a bisphenol A type epoxy resin because it is used in a wide range of applications and has low manufacturing costs.
[0021] The adhesive composition may contain one type of epoxy resin (A) or may contain two or more types of epoxy resins (A). When the adhesive composition contains multiple types of epoxy resins (A), these epoxy resins (A) may be, for example, epoxy resins containing the same repeating unit but having different epoxy equivalents, or may be epoxy resins containing different repeating units. In this way, by using multiple types of epoxy resins (A) in combination, the glass transition temperature and crosslink density of the cured product of the adhesive composition can be adjusted.
[0022] The content of the epoxy resin (A) in the adhesive composition may take various forms as long as the adhesive composition is curable and the cured product of the adhesive composition can be imparted with vitrimer properties. For example, the adhesive composition may have a composition in which the mass ratio of the epoxy resin (A) is the largest among the epoxy resin (A), the acid anhydride curing agent (B), the transesterification catalyst (C), and the polymer (D).
[0023] [Acid anhydride curing agent (B)] The adhesive composition may contain one type of acid anhydride curing agent (B) or two or more types of acid anhydride curing agents (B). The acid anhydride curing agent (B) may be any substance that cures the epoxy resin (A), and a substance that contributes to the crosslinking reaction and / or chain extension reaction between epoxy groups in the epoxy resin (A) can be used as the acid anhydride curing agent (B). Examples of such substances include compounds known as acid anhydride curing agents for epoxy resins. In addition, among substances generally called "curing accelerators" for epoxy resins, substances that contribute to the crosslinking reaction and / or chain extension reaction between epoxy groups in the epoxy resin (A) can also be used as the acid anhydride curing agent (B).
[0024] More specifically, examples of the acid anhydride curing agent (B) include glutaric acid, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, trimellitic anhydride, and condensates of maleic anhydride and an unsaturated compound.
[0025] The content of the acid anhydride curing agent (B) in the adhesive composition may take various forms as long as the adhesive composition is curable and the cured product of the adhesive composition can be imparted with the properties of a vitrimer. From the viewpoint of more reliably improving adhesive properties such as adhesive strength and more reliably imparting the properties of a vitrimer to the cured product of the adhesive composition, the content of the acid anhydride curing agent (B) is preferably 0.1 parts by mass or more and 300 parts by mass or less, more preferably 0.1 parts by mass or more and 250 parts by mass or less, even more preferably 0.1 parts by mass or more and 200 parts by mass or less, and particularly preferably 0.1 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the epoxy resin.
[0026] [Transesterification catalyst (C)] The adhesive composition may contain one type of transesterification catalyst (C), or may contain two or more types of transesterification catalysts (C). As the transesterification catalyst (C), a compound having an effect of promoting the transesterification reaction can be used. As the transesterification catalyst (C), for example, an alkali metal compound such as an organic acid salt, an inorganic salt, an oxide, a hydroxide, a hydride, and an alkoxide of an alkali metal; an alkaline earth metal compound such as an organic acid salt, an inorganic salt, an oxide, a hydroxide, a hydride, and an alkoxide of an alkaline earth metal compound; a nitrogen-containing compound such as a quaternary ammonium hydroxide, a quaternary ammonium hydroxide salt, and an amine can be used.
[0027] Salts of zinc, tin, zirconium and lead can also be used as the transesterification catalyst (C). These metal salts can be used alone or in combination with the above-mentioned alkali metal compounds and alkaline earth metal compounds.
[0028] More specifically, examples of the transesterification catalyst (C) include sodium carbonate, sodium hydrogen carbonate, cesium carbonate, zinc acetate, zinc benzoate, zinc 2-ethylhexanoate, tin chloride (II), tin chloride (IV), tin acetate (II), tin acetate (IV), dibutyltin dilaurate, dibutyltin oxide, dibutyltin dimethoxide, zirconium acetylacetonate, zirconium oxyacetate, zirconium tetrabutoxide, lead acetate (II), lead acetate (IV), zirconium acetate, and titanium tetrabutoxide. Among these compounds, from the viewpoint of reaction efficiency, it is preferable to use zinc acetylacetonate as the transesterification catalyst (C). In addition, from the viewpoints of catalytic effect, price, distribution volume, and influence on the color of the cured product, it is preferable to use sodium carbonate and / or sodium hydrogen carbonate as the transesterification catalyst (C).
[0029] The content of the transesterification catalyst (C) in the adhesive composition can take various forms as long as the adhesive composition is curable and the cured product of the adhesive composition can be imparted with vitrimer properties. The content of the transesterification catalyst (C) in the adhesive composition is preferably 0.01% by mass or more and 20% by mass or less relative to the mass of the adhesive composition.
[0030] [Polymer (D) Having an Ester Exchangeable Group] The adhesive composition contains a polymer (D) having an ester exchangeable group. The polymer (D) is configured so that ester exchange can be performed between the ester exchangeable group in the polymer (D) and a hydroxyl group generated by ring-opening of an epoxy group contained in the epoxy resin (A), and a group such as an ester group or a carboxyl group generated by ring-opening of an acid anhydride group contained in the acid anhydride curing agent (B). The adhesive composition may contain one type of polymer (D) or may contain two or more types of polymers (D).
[0031] The polymer (D) may be a thermosetting polymer or a thermoplastic polymer so long as it is configured to be capable of transesterification. The transesterifiable group in the polymer (D) is not particularly limited as long as it is a group capable of transesterification. In this specification, the "transesterifiable group" includes, for example, a monovalent group such as a hydroxyl group or a carboxyl group, and a divalent group such as an ester group (ester bond). The transesterifiable group in the polymer (D) is preferably at least one group selected from the group consisting of an ester group, a hydroxyl group, and a carboxyl group, and more preferably an ester group.
[0032] The transesterifiable group may be contained in the main chain or in the side chain of the polymer (D). As the polymer (D) having a transesterifiable group in the main chain, for example, polycaprolactone (D1) having an ester group in the main chain is preferably used. As the polymer (D) having a transesterifiable group in the side chain, for example, polyrotaxane (D2) having an ester group in the side chain is preferably used. These polymers (D) can further improve the adhesive properties of the cured product of the adhesive composition. From the viewpoint of more easily obtaining such an effect, it is more preferable that the adhesive composition contains polyrotaxane (D2) having an ester group as the polymer (D).
[0033] The content of the polymer (D) in the adhesive composition is preferably 0.1% by mass or more and 30% by mass or less based on the mass of the adhesive composition, in which case the effect of improving the adhesive properties can be more reliably obtained.
[0034] [Polycaprolactone (D1)] The polycaprolactone (D1) used as the polymer (D) is a polymer based on a repeating unit derived from caprolactone, and has an ester group as an ester exchangeable group in its main chain. The polycaprolactone (D1) may be composed only of a repeating unit derived from caprolactone. In addition, the terminals of the polycaprolactone (D1) may be modified with various functional groups as necessary to improve compatibility with the epoxy resin (A) and adhesive properties.
[0035] The number average molecular weight of the polycaprolactone (D1) contained in the adhesive composition is preferably 10,000 or more, more preferably 30,000 or more. In this case, the effect of improving the adhesive properties can be more reliably obtained. The number average molecular weight of the polycaprolactone (D1) is preferably 500,000 or less, more preferably 300,000 or less.
[0036] In configuring the preferred range of the number average molecular weight of polycaprolactone (D1), the upper and lower limits of the number average molecular weight of polycaprolactone (D1) described above can be combined arbitrarily. For example, the preferred range of the number average molecular weight of polycaprolactone (D1) may be 10,000 or more and 500,000 or less, or 30,000 or more and 300,000 or less.
[0037] The number average molecular weight of polycaprolactone (D1) is specifically a polystyrene-equivalent number average molecular weight obtained by gel permeation chromatography (GPC). The number average molecular weight of polycaprolactone (D1) is obtained, for example, by using a test solution having a solid content concentration of 0.1 mass % obtained by dissolving polycaprolactone (D1) in chloroform and measuring under the following conditions.
[0038] Analytical equipment: Shimadzu Corporation HPLC system Column: Shodex (registered trademark) GPC LF-G x 1 + Shodex GPC LF-804 x 1 (both manufactured by Showa Denko K.K.) Test temperature: 40℃ ·Eluent flow rate: 1.0mL / min
[0039] The content of polycaprolactone (D1) in the adhesive composition is preferably 0.1% by mass or more and 30% by mass or less, based on the mass of the adhesive composition, in which case the effect of improving the adhesive properties can be more reliably obtained.
[0040] [Polyrotaxane (D2)] The polyrotaxane (D2) used as the polymer (D) is composed of a polyrotaxane having a cyclic molecule and a linear molecule that is encapsulated in the ring of the cyclic molecule and has a blocking group at both ends. The molecular structure of the polyrotaxane (D2) contains an ester group as a group capable of transesterification.
[0041] Polyrotaxane (D2) has at least a linear molecule, a cyclic molecule, and a blocking group. The linear molecule and the cyclic molecule in polyrotaxane (D2) are themselves composed of a polymer compound. The linear molecule in polyrotaxane (D2) is pierced by the cyclic molecule and is included in the polyrotaxane.
[0042] The capping groups in the polyrotaxane (D2) are arranged at both ends of the linear molecule. More specifically, the capping groups in the polyrotaxane (D2) are bonded to both ends of the linear molecule. The capping groups can prevent the cyclic molecules from being detached from the ends of the linear molecule. The capping groups only need to be large enough to prevent the cyclic molecules from being detached from the ends of the linear molecule. More specifically, the capping groups have a maximum length larger than the diameter of the opening of the cyclic molecules.
[0043] The molecular structure of polyrotaxane (D2) contains an ester group. The ester group may be contained in at least one of the linear molecule, the cyclic molecule, and the terminal group. The linear molecule, the cyclic molecule, and the terminal group constituting polyrotaxane (D2) are described in more detail below.
[0044] ·Linear molecule Examples of the linear molecule in the polyrotaxane (D2) include cellulose-based resins such as carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose; polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyvinyl acetal resins, polyvinyl methyl ether, polyamine, polyethyleneimine, casein, gelatin, starch, and copolymers containing two or more types of repeating units among the repeating units constituting these polymers.
[0045] Examples of linear molecules include polyolefin resins such as polyethylene and polypropylene; polystyrene resins such as polystyrene and acrylonitrile-styrene copolymers; acrylic resins such as polymethyl methacrylate, (meth)acrylic acid ester copolymers and acrylonitrile-methyl acrylate copolymers; polyester resins, polyvinyl chloride resins, polycarbonate resins, polyurethane resins, vinyl chloride-vinyl acetate copolymers, polyvinyl butyral resins, and derivatives or modified products thereof.
[0046] Further, examples of linear molecules include polysiloxanes such as polydimethylsiloxane; polydienes such as polyisoprene and polybutadiene; polyamides such as nylon; polyisobutylene, polyaniline, acrylonitrile-butadiene-styrene copolymer (i.e., ABS resin), polyimides, polysulfones, polyimines, polyacetic anhydrides, polyureas, polysulfides, polyphosphazenes, polyketones, polyphenylenes, polyhaloolefins, and derivatives thereof.
[0047] As the linear molecule, polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc.; polyolefin resins such as polyethylene, polypropylene, etc.; polysiloxanes such as polydimethylsiloxane, etc. are preferred, and polyethylene glycol is more preferred.
[0048] The number average molecular weight of the linear molecule is preferably 1,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more. The upper limit of the molecular weight of the linear molecule is not particularly limited, but is about 1 million from the viewpoint of handling. The number average molecular weight of the linear molecule is measured, for example, in accordance with JIS K7252-1:2016.
[0049] Cyclic molecules The cyclic molecule has a cyclic main chain made of a polymer. As the main chain of the cyclic molecule, for example, cyclodextrins such as α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, and derivatives thereof can be used.
[0050] It is preferable that the linear molecule of the polyrotaxane (D2) is polyethylene glycol and the cyclic molecule is α-cyclodextrin. In this case, the synthesis of the polyrotaxane (D2) is easy, and the effect of improving the mechanical properties by the polyrotaxane (D2) is easily obtained.
[0051] From the viewpoint of facilitating the movement of the cyclic molecules along the linear molecules, the inclusion amount of the cyclic molecules in the polyrotaxane (D2) is preferably 0.6 or less, more preferably 0.5 or less, and even more preferably 0.4 or less. On the other hand, from the viewpoint of facilitating the manifestation of the effect of improving the mechanical properties by the polyrotaxane (D2), the inclusion amount is preferably 0.001 or more, more preferably 0.01 or more, and even more preferably 0.05 or more.
[0052] The inclusion amount of the cyclic molecule is expressed as a relative value when the maximum amount of the cyclic molecule that can include one linear molecule (i.e., the maximum inclusion amount) is set to 1. The maximum inclusion amount of the cyclic molecule can be determined based on the length of the linear molecule and the thickness of the cyclic molecule. For example, the maximum inclusion amount of the cyclic molecule when the linear molecule is polyethylene glycol and the cyclic molecule is α-cyclodextrin has been experimentally determined (see Macromolecules 1993, 26, p. 5698-5703).
[0053] In addition, when configuring a preferred range of the amount of the cyclic molecule included, the upper and lower limits of the amount of the cyclic molecule included can be combined arbitrarily. For example, the preferred range of the cyclic molecule may be 0.001 to 0.6, 0.01 to 0.5, or 0.05 to 0.4.
[0054] The cyclic molecule may have a cyclic structure and an external stimulus reaction type ring-opening functional group that has the property of opening the ring structure in response to an external stimulus such as heat, light, etc. The external stimulus reaction type ring-opening functional group is composed of, for example, a cyclic aliphatic ether and / or a cyclic aliphatic thioether.
[0055] The cyclic molecule may have a side chain bonded to the main chain. In this case, the side chain may be bonded to the main chain via, for example, the above-mentioned external stimulus-responsive ring-opening functional group.
[0056] From the viewpoint of further increasing the reactivity of the transesterification reaction, it is preferable that the side chain of the cyclic molecule contains an ester group. From the same viewpoint, it is preferable that the side chain contains a structural unit derived from a polyester, and more preferably a structural unit derived from an aliphatic polyester. In addition, by using an aliphatic polyester among polyesters as the side chain, it is possible to further increase the compatibility with the epoxy resin.
[0057] Examples of aliphatic polyesters include polylactic acid, polyglycolic acid, poly(3-hydroxybutyrate), poly(4-hydroxybutyrate), poly(3-hydroxybutyrate / 3-hydroxyvalerate), and polycaprolactone. Among these, polycaprolactone is preferred from the viewpoint of compatibility with epoxy resins, and specifically, poly(ε-caprolactone) is more preferred.
[0058] The number average molecular weight of the side chain of the cyclic molecule is preferably 500 or more. In this case, the mechanical properties of the adhesive composition can be more easily improved. In addition, the number average molecular weight of the side chain of the cyclic molecule is preferably 100,000 or less. In this case, the reactivity of the transesterification reaction can be further increased, and the compatibility with the epoxy resin (A) can be further increased.
[0059] ·Closing group The blocking group is not particularly limited as long as it is a group that has the effect of preventing the cyclic molecule from being detached from the linear molecule. Examples of the blocking group include dinitrophenyl groups, cyclodextrins, adamantane groups, trityl groups, fluoresceins, pyrenes, benzenes having a substituent, polycyclic aromatics that may have a substituent, and steroids. In addition, examples of the substituents in benzenes and polycyclic aromatics include alkyl groups, alkyloxy groups, hydroxy groups, halogen groups, cyano groups, sulfonyl groups, carboxy groups, amino groups, and phenyl groups. One or more substituents may be present.
[0060] As the blocking group, dinitrophenyl groups, cyclodextrins, adamantane groups, trityl groups, fluoresceins, and pyrenes are preferably used, and adamantane groups and trityl groups are more preferably used.
[0061] ·Manufacturing method The method for producing the polyrotaxane (D2) may take various forms. For example, the polyrotaxane (D2) can be produced by a production method including the following three steps, steps (1) to (3). Step (1): A step of obtaining a linear molecule having linking groups at both ends capable of bonding to capping groups. Step (2): A step of mixing cyclic molecules and linear molecules, and passing the linear molecules through the rings of the cyclic molecules to obtain a polyrotaxane (pseudopolyrotaxane) having no capping groups. Step (3): A step of obtaining a polyrotaxane by blocking the linking groups at both ends of the linear molecule with the blocking groups while maintaining the linear molecule in a state where it is encapsulated by the cyclic molecule.
[0062] In the step (1), a linear molecule having linking groups at both ends is obtained. For example, when a linear molecule having linking groups at both ends is available, the linear molecule can be used to carry out the step (2).
[0063] Alternatively, a linear molecule having a linking group can be obtained by starting a linear molecule having no linking group at both ends and converting the groups present at both ends of the linear molecule into linking groups. In this case, the method for converting the terminal group into a linking group is not particularly limited, and a conversion method using a derivatization method utilizing a normal organic synthesis can be used. The conversion from the terminal group to the linking group may be performed in one step or in multiple steps.
[0064] In the step (2), the linear molecule and the cyclic molecule are mixed to obtain a pseudo-polyrotaxane in which the linear molecule is enclosed by the cyclic molecule. The method for forming the pseudo-polyrotaxane is not particularly limited, but for example, the pseudo-polyrotaxane can be formed in the solution by dissolving an excess of the linear molecule in a saturated solution of the cyclic molecule. In addition, the pseudo-polyrotaxane can be formed in the solution by, for example, dissolving the linear molecule and the cyclic molecule in an organic solvent or a mixed solvent of an aqueous solution and an organic solvent, and allowing the obtained solution to stand as it is, or applying ultrasonic vibration to the obtained solution for several hours to several tens of hours.
[0065] The pseudo-polyrotaxane can be obtained by removing the solvent from the solution containing the pseudo-polyrotaxane thus obtained. The method for removing the solvent is not particularly limited, and the solvent may be removed by adopting a known method such as centrifugation, freeze-drying, hot air drying, reduced pressure distillation, reduced pressure drying, and vacuum drying. In addition, the purity of the pseudo-polyrotaxane can be increased by washing the pseudo-polyrotaxane obtained after removing the solvent.
[0066] In the step (2), the amount of the cyclic molecules included in the pseudopolyrotaxane can be controlled by various methods. More specifically, for example, the amount of the cyclic molecules included can be controlled within a desired range by appropriately adjusting the time, humidity, temperature, pressure, and molecular weight of the linear molecule used when mixing the cyclic molecules and the linear molecule.
[0067] In the step (3), the linking groups at both ends of the linear molecule are blocked with blocking groups while preventing the cyclic molecules from being detached from the linear molecule, thereby obtaining polyrotaxane (D2). A typical organic synthesis reaction can be used to introduce blocking groups to the ends of the linear molecule. The solvent used in the reaction to introduce the blocking groups may be appropriately selected, and examples of the solvent include dimethylformamide and acetonitrile.
[0068] When none of the linear molecule, cyclic molecule, and capping group used in the synthesis of the polyrotaxane (D2) has an ester group, step (4) of introducing an ester group into the polyrotaxane (D2) may be carried out after steps (1) to (3).
[0069] In the step (4), for example, an ester group can be introduced into the polyrotaxane (D2) by modifying the main chain of the cyclic molecule of the polyrotaxane with a side chain containing an ester group. A normal organic synthesis reaction can be used to introduce the side chain into the main chain. In addition, a solvent may or may not be used when introducing the side chain. When a solvent is used, for example, dimethylformamide, dimethylsulfoxide, acetonitrile, etc. can be used.
[0070] The content of the polyrotaxane (D2) in the adhesive composition is preferably 0.1% by mass or more and 30% by mass or less based on the mass of the adhesive composition, in which case the effect of improving the adhesive properties can be more reliably obtained.
[0071] (Adhesive Composition) The adhesive composition contains an epoxy resin (A), an acid anhydride curing agent (B), an ester exchange catalyst (C), and a polymer having an ester exchangeable group (D). In preparing the adhesive composition, the above-mentioned components may be mixed by a method commonly used in this field.
[0072] The adhesive composition is configured to be cured by applying heat. The degree of curing of the adhesive composition may be appropriately set depending on the desired physical properties, applications, etc. The degree of curing of the adhesive composition can be controlled by the curing method of the adhesive composition, more specifically, the heating conditions when curing the adhesive composition.
[0073] The heating conditions for curing the adhesive composition vary depending on the components and amounts in the composition. For example, the adhesive composition can be cured by appropriately setting the heating temperature within the range of 80°C to 200°C and the heating time within the range of 1 hour to 24 hours. When the curing reaction of the adhesive composition is to be sufficiently promoted, for example, the adhesive composition may be heated in two stages. In this case, for example, the heating temperature in the first stage may be 80°C to 160°C and the heating time may be 10 minutes to 30 minutes, and the heating temperature in the second stage may be 120°C to 200°C and the heating time may be 1 hour to 24 hours.
[0074] Furthermore, when attempting to obtain a semi-cured product of the adhesive composition, the curing reaction of the adhesive composition may be allowed to proceed to an extent that allows the adhesive composition to maintain its shape by heating or the like.
[0075] [Adhesive properties] The adhesive composition has excellent adhesive properties and various properties such as easy dismantling and re-adhesion. The adhesive strength of the adhesive composition can be measured based on the results of a tensile test. For example, the tensile shear adhesion test according to JIS K6850:1999 can be used as a method for measuring the adhesive strength of the adhesive composition.
[0076] The adhesive composition preferably has adhesive properties such that a test piece obtained by bonding an adherend made of aluminum with the adhesive composition has a tensile shear adhesive strength of 20 MPa or more at 25° C. In this case, the adhesive composition can also be used in applications requiring high adhesive strength, such as structural materials.
[0077] In addition, if the adhesive composition is configured such that the adhesive strength is significantly reduced by an external stimulus such as heat, light, or solvent spray after adhering to the adherend, the adherend can be easily separated and dismantled. Such an adhesive composition having easy dismantling property can improve the maintenance property when repairing a specific part, etc., and the recyclability when dismantling a waste product. From this viewpoint, it is preferable that the adhesive composition has an adhesive property such that the tensile shear adhesive strength of the adhesive composition at 200°C is less than 10% of the tensile shear adhesive strength of the adhesive composition at 25°C. From the same viewpoint, it is more preferable that the adhesive composition has an adhesive property such that the tensile shear adhesive strength of the adhesive composition at 200°C is less than 7% of the tensile shear adhesive strength of the adhesive composition at 25°C.
[0078] Furthermore, if the adhesive composition is configured to be capable of re-adhering the adherend after peeling it off, it is possible to improve the ease of maintenance when repairing a particular part, etc., or when reassembling recycled parts. From this viewpoint, it is preferable that the adhesive composition has adhesive properties such that, when a tensile shear bond strength test is performed on a test piece using the adhesive composition, the test piece is broken, and two adherends obtained are re-adhered via a cured product of the adhesive composition, the tensile shear bond strength at 25°C is 12 MPa or more.
[0079] The adhesive composition also has excellent thermal stress relaxation properties, and can relieve thermal stress caused by the difference in thermal expansion coefficients when, for example, adhering materials with different thermal expansion coefficients are bonded together, thereby reducing warping of the bonded body. Such stress relaxation properties can be evaluated, for example, based on the amount of warping of the adherends after bonding different materials together.
[0080] In addition, it is extremely important that the adhesive composition can be washed with a solvent or the like and removed from the adherend after peeling off the adherend, in repairing a specific part or recycling the adherend. Usually, a thermosetting or photocurable adhesive (resin) made of an epoxy resin or the like is insoluble in a solvent and is therefore difficult to wash, but the adhesive composition can be easily washed from the adherend with a solvent or the like after an adhesion test. On the other hand, if the adhesive composition can be washed with a solvent in its normal use environment, this means that the solvent resistance is low, and there is a risk that the environment in which it can be used will be limited. Therefore, from the viewpoint of broadening the range of environments in which the adhesive composition can be used, it is desirable that the adhesive composition is configured to be washed under conditions other than the normal use range. Examples of conditions other than the normal use range include temperature, humidity, pressure, etc., but control by temperature is practical. In the case of temperature, it is preferable that the washability is exhibited at a temperature of 50°C or higher, more preferably 150°C or higher. The solvent is not limited as long as it can dissolve and wash the adhesive composition, but when the adhesive composition is a vitrimer, it is effective to wash the adhesive composition with alcohol.
[0081] [Application] The adhesive composition has high adhesive strength, excellent thermal stress relaxation properties, and easy dismantling and re-adhesion properties, and can therefore be widely used for bonding various structural materials and various members.
[0082] For example, the adhesive composition comprises a first member and A second member; and a cured adhesive material interposed between the first member and the second member, The adhesive cured product can be applied to the production of a bonded body, in which the adhesive cured product is a cured product of the adhesive composition.
[0083] In one embodiment of the bonded body, the second member may be made of a material different from that of the first member. As described above, the adhesive composition has excellent thermal stress relaxation properties. Therefore, when the first member and the second member are made of different materials, the adhesive composition can be used to bond these members, thereby relaxing the stress caused by the difference in thermal expansion coefficient between the first member and the second member, and reducing warping of the bonded body.
[0084] In another embodiment of the bonded body, the second member may be made of the same material as the first member.
[0085] (Method of Manufacturing Joint) The method for producing a bonded body includes curing the adhesive composition in a state in which the adhesive composition is interposed between the first member and the second member. In the method for producing a bonded body, the method for interposing the adhesive composition between the first member and the second member may take various forms.
[0086] For example, in the manufacturing method, the adhesive composition may be brought into contact with a first member and then the adhesive composition may be brought into contact with a second member, thereby providing the adhesive composition between the first member and the second member. Also, the adhesive composition may be brought into contact with the first member and the second member simultaneously, thereby providing the adhesive composition between the first member and the second member.
[0087] The adhesive composition is cured, for example, by the reaction of the acid anhydride curing agent (B) with the epoxy groups in the epoxy resin (A). At this time, in order to promote the curing of the adhesive composition, the adhesive composition may be heated as necessary.
[0088] (Adhesion method) From another point of view, the above-mentioned method for producing a bonded body can also be understood as an adhesion method for bonding a first member and a second member by using the adhesive composition. That is, the adhesion method includes the steps of contacting the first member and the second member with the adhesive composition, and promoting a transesterification reaction between the epoxy resin (A) and the polymer (D).
[0089] In the bonding method, the adhesive composition may be brought into contact with a first member and then the adhesive composition may be brought into contact with a second member, or the adhesive composition may be brought into contact with the first member and the second member simultaneously.
[0090] In the adhesion method, the transesterification reaction can be promoted by using an adhesive composition containing a transesterification catalyst (C). In the adhesion method, the adhesive composition may be heated as necessary to further promote the transesterification reaction.
[0091] Furthermore, the adhesive composition is useful, for example, for peeling and re-adhesion of component parts in the process of repairing a product, or for disassembly when recycling waste products, taking advantage of its properties such as easy dismantling and re-adhesion. EXAMPLES
[0092] Examples of the adhesive composition are described below. Note that the specific aspects of the adhesive composition, adhesive cured product, and bonded body according to the present invention are not limited to those of the examples, and the configurations can be appropriately changed without departing from the spirit of the present invention.
[0093] The raw materials for the adhesive composition prepared in this example are as follows:
[0094] (raw materials) Epoxy resin (a): Bisphenol A type liquid epoxy resin ("jER (registered trademark) 828" manufactured by Mitsubishi Chemical Corporation) Acid anhydride hardener (b): Glutaric anhydride (Tokyo Chemical Industry Co., Ltd.) Amine-based hardener (e): 4,4'-diaminodiphenylmethane (Tokyo Chemical Industry Co., Ltd.) Transesterification catalyst (c): zinc acetylacetonate hydrate (Sigma-Aldrich) Polycaprolactone (d1): Polycaprolactone (number average molecular weight: 70,000 to 90,000, manufactured by Sigma-Aldrich) Polyrotaxane (d2): Polycaprolactone-modified hydroxypropylated polyrotaxane
[0095] The method for preparing polyrotaxane (d2) is the same as that described in paragraphs
[0035] to
[0037] of the specification of Japanese Patent No. 4461252 and paragraphs
[0072] to
[0073] of the specification of JP-A-2011-046917. The structure of polyrotaxane (d2) thus obtained is as follows.
[0096] Linear molecule: Polyethylene glycol (number average molecular weight 35,000) · Main chain of cyclic molecule: α-cyclodextrin Side chain of cyclic molecule: Polycaprolactone (number of caprolactone structural units: about 8) Capping group: Adamantane amine group - Inclusion amount of cyclic molecules: 0.28 Number of side chains per cyclic molecule: Approx. 5 Weight average molecular weight of polyrotaxane (d2): 700,000
[0097] Example 1 4.6% by mass of the transesterification catalyst (c) was added to 65.6% by mass of the epoxy resin (a), and the mixture was mixed at a temperature of 140°C for 10 minutes to uniformly disperse the transesterification catalyst (c) in the epoxy resin (a). Then, 10.0% by mass of polycaprolactone (d1) was added to 70.2% by mass of the mixture of the epoxy resin (a) and the transesterification catalyst (c), and the mixture was mixed at a temperature of 160°C for 10 minutes. This mixture was degassed under reduced pressure at a temperature of 160°C for 10 minutes. Then, 19.8% by mass of an acid anhydride-based curing agent was added to 80.2% by mass of the mixture, and the mixture was mixed at a temperature of 140°C for 5 minutes. Then, the mixture was degassed under reduced pressure for 5 minutes to obtain the adhesive composition of Example 1.
[0098] Example 2 4.6% by mass of the transesterification catalyst (c) was added to 65.6% by mass of the epoxy resin (a), and the mixture was mixed at a temperature of 140°C for 10 minutes to uniformly disperse the transesterification catalyst (c) in the epoxy resin (a). Then, 10.0% by mass of the polyrotaxane (d2) was added to 70.2% by mass of the mixture of the epoxy resin (a) and the transesterification catalyst (c), and the mixture was mixed at a temperature of 140°C for 10 minutes. This mixture was degassed under reduced pressure at a temperature of 140°C for 10 minutes. Then, 19.8% by mass of the acid anhydride-based curing agent (b) was added to 80.2% by mass of the mixture, and the mixture was mixed at a temperature of 140°C for 5 minutes. Then, the mixture was degassed under reduced pressure for 5 minutes to obtain an adhesive composition of Example 2.
[0099] Comparative Example 1 5.1% by mass of the transesterification catalyst (c) was added to 72.9% by mass of the epoxy resin (a), and the mixture was mixed at a temperature of 140°C for 10 minutes to uniformly disperse the transesterification catalyst (c) in the epoxy resin (a). This mixture was degassed under reduced pressure for 10 minutes at a temperature of 140°C. Then, 22.0% by mass of the acid anhydride curing agent (b) was added to 78.0% by mass of the mixture, and the mixture was mixed at a temperature of 140°C for 5 minutes. Then, the mixture was degassed under reduced pressure for 5 minutes to obtain an adhesive composition of Comparative Example 1.
[0100] Comparative Example 2 20.8% by mass of the amine-based curing agent (e) was added to 79.2% by mass of the epoxy resin (a), and mixed for 10 minutes at a temperature of 85° C. In this manner, an adhesive composition of Comparative Example 2 was obtained.
[0101] Next, the adhesive compositions of the Examples and Comparative Examples were used to evaluate adhesive strength, ease of dismantling, re-adhesion, stress relaxation, and removability of the cured product with a solvent by the following methods.
[0102] (Adhesive strength) The evaluation of adhesive strength was carried out based on the tensile shear adhesive strength at 25° C. First, a test piece to be used for the tensile shear adhesive strength was prepared by the following method.
[0103] [Preparation of test pieces] An aluminum plate (material: A5052P, width: 25 mm, length: 100 mm, thickness: 1.6 mm) as an adherend was immersed in hydrochloric acid with a concentration of 2% by mass, left to stand for 10 minutes, and then thoroughly washed with distilled water. The aluminum plate was then immersed in an aqueous solution of a silane coupling agent with a concentration of 1% by mass for 10 minutes. For the aluminum plate used to evaluate the adhesive compositions of Examples 1 and 2 and Comparative Example 1, 3-glycidyloxypropyltrimethoxysilane (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as a silane coupling agent. For the aluminum plate used to evaluate the adhesive composition of Comparative Example 2, 3-aminopropyltrimethoxysilane (manufactured by Tokyo Chemical Industry Co., Ltd.) was used as a silane coupling agent.
[0104] After removing the aluminum plate from the aqueous solution of the silane coupling agent, the excess aqueous solution of the silane coupling agent attached to the surface of the aluminum plate was wiped off with a paper towel. The aluminum plate was then heated at a temperature of 120°C for 10 minutes to react with the aluminum plate and the silane coupling agent. An adherend was obtained in this manner.
[0105] Next, two adherends were bonded using the adhesive composition to prepare a test piece having a shape conforming to the provisions of JIS K6850:1999. The adhesive compositions of Examples 1-2 and Comparative Example 1 were cured by holding the test piece at a temperature of 140°C under atmospheric pressure for 18 hours. The adhesive composition of Comparative Example 2 was cured by heating the test piece in two stages as follows. That is, in the first stage of heating, the test piece was heated from room temperature to a temperature of 90°C at a rate of 6°C / min under atmospheric pressure, and then held at a temperature of 90°C for 15 minutes. In the second stage of heating, the test piece was heated from 90°C to 150°C at a rate of 6°C / min, and then held at a temperature of 150°C for 2 hours.
[0106] [Tensile shear adhesion test] The test pieces prepared by the above method were used to carry out a tensile test in accordance with the method specified in JIS K6850:1999. A precision universal testing machine (Shimadzu Corporation's "Autograph (registered trademark) AG-10kNXPlus") was used for the test. The test temperature was 25°C and the crosshead speed was 2 mm / min. The maximum load from the start of the tensile test to the breakage of the cured adhesive composition was divided by the adhesive area to calculate the tensile shear adhesive strength. The tensile shear adhesive strengths at 25°C of the adhesive compositions of the Examples and Comparative Examples are as shown in Table 1.
[0107] (Easy disassembly) The evaluation of the ease of dismantling was performed based on the tensile shear adhesive strength at 200°C. The method for preparing the test pieces used for the tensile shear adhesive strength was the same as the method for preparing the test pieces used for the evaluation of adhesive strength described above. The method for measuring the tensile shear adhesive strength at 200°C was the same as the method for measuring the tensile shear adhesive strength at 25°C, except that the test temperature in the tensile test was 200°C. The tensile shear adhesive strengths at 200°C of the adhesive compositions of the Examples and Comparative Examples were as shown in Table 1.
[0108] (Re-adhesion) The re-adhesion evaluation was performed based on the tensile shear adhesive strength after re-adhesion. First, the test piece was broken by the tensile test in the above-mentioned evaluation of the ease of dismantling, and two adherends to which the cured product of the adhesive composition was attached were prepared. These adherends were overlapped and hot-pressed to prepare test pieces to be used in the evaluation of re-adhesion. The temperature in the hot press was 200°C, the load was 10 kN, and the press time was 2.5 hours.
[0109] Using the test pieces thus obtained, a tensile test was carried out in the same manner as in the evaluation of adhesive strength described above, and the tensile shear adhesive strength after re-adhesion was measured. Based on the tensile shear adhesive strength thus obtained, re-adhesion was evaluated. The tensile shear adhesive strength after re-adhesion of the adhesive compositions of the Examples and Comparative Examples was as shown in Table 1.
[0110] (Evaluation of stress relaxation properties) The stress relaxation property was evaluated based on the amount of warping of a bonded body obtained by bonding dissimilar metals using the adhesive composition. First, 1% by mass of glass beads ("BZ-06" manufactured by AS ONE Corporation, particle size: 0.50 to 0.71 mm) was mixed with the adhesive composition to prepare an adhesive composition to be used for evaluating the stress relaxation property. Separately, an aluminum plate (material: A5052P, width: 25 mm, length: 100 mm, thickness: 1.6 mm) and a steel plate (material: SPCC-SB, width: 25 mm, length: 100 mm, thickness: 1.6 mm) were prepared, and the surfaces of these plates were degreased using acetone and hexane to prepare an adherend.
[0111] Next, the adhesive composition was applied to the entire surface of one side of the aluminum plate, and then a steel plate was placed on the adhesive composition to obtain a laminate. A jig was attached to the outer periphery of this laminate, and the laminate was heated under atmospheric pressure while the aluminum plate and the steel plate were fixed, thereby curing the adhesive composition. As a result, a bonded body was obtained. The adhesive compositions of Examples 1 to 2 and Comparative Example 1 were cured by holding the laminate at a temperature of 140°C under atmospheric pressure for 18 hours. The adhesive composition of Comparative Example 2 was cured by heating the laminate in two stages as follows. That is, in the first stage of heating, the laminate was heated from room temperature to a temperature of 90°C at a rate of 6°C / min under atmospheric pressure, and then the temperature of 90°C was held for 15 minutes. In the second stage of heating, the laminate was heated from 90°C to 150°C at a rate of 6°C / min, and then the temperature of 150°C was held for 2 hours.
[0112] The bonded body thus obtained is curved overall due to the difference in thermal expansion coefficient between the aluminum plate and the steel plate, with the surface of the steel plate being convex and the surface of the aluminum plate being concave.
[0113] Next, the bonded body was placed on a reference plane with the aluminum plate facing downward. The heights from the reference plane were measured at five positions, including the four corners of the bonded body and the center of the bonded body, i.e., the intersection of the diagonal lines. The average value of the heights of the four corners was subtracted from the height of the center of the bonded body to calculate the amount of warping of the bonded body. The amounts of warping of the bonded bodies obtained using the adhesive compositions of the Examples and Comparative Examples were as shown in Table 1.
[0114] (Evaluation of removability of cured product with solvent) In the above-mentioned tensile shear adhesion test, two adherends to which the cured product of the adhesive composition was attached, which had been broken by the tensile test, were immersed in ethylene glycol at 180°C for 2 hours and 30 minutes. After the adherends were removed from the ethylene glycol and dried, the surfaces of the adherends were visually observed to evaluate the presence or absence of the adhesive composition. In addition, the surfaces of the adherends were measured by infrared spectroscopy (total reflection measurement method) to evaluate the presence or absence of peaks derived from the cured product of the adhesive composition. Based on these results, the presence or absence of the cured product of the adhesive composition on the surface of the adherend was evaluated. The evaluation results of the removability of the cured product by a solvent for the adhesive compositions of the examples and comparative examples are as shown in Table 1.
[0115] [Table 1]
[0116] As shown in Table 1, the adhesive composition of Example 1 contains an epoxy resin (a), an acid anhydride curing agent (b), an ester exchange catalyst (c) and polycaprolactone (d1). Therefore, the adhesive composition of Example 1 had a high tensile shear adhesive strength at 25°C, and exhibited excellent adhesive properties. In addition, the adhesive composition of Example 1 had a low tensile shear adhesive strength at 200°C, and had a high tensile shear adhesive strength after re-adhesion, and exhibited easy dismantling and re-adhesion. Furthermore, in an evaluation of the removability of the cured product by a solvent, the cured product of the adhesive composition of Example 1 was removed from the surface of the adherend by washing with ethylene glycol at 180°C. From this result, it can be understood that the adhesive composition of Example 1 has good removability of the cured product by a solvent.
[0117] The adhesive composition of Example 2 contains an epoxy resin (a), an acid anhydride curing agent (b), an ester exchange catalyst (c) and a polyrotaxane (d2). Therefore, the adhesive composition of Example 2 has a high tensile shear adhesive strength at 25°C, and exhibits excellent adhesive properties. In addition, the adhesive composition of Example 2 has a low tensile shear adhesive strength at 200°C, and has a high tensile shear adhesive strength after re-adhesion, and exhibits easy dismantling and re-adhesion. Furthermore, in an evaluation of the removability of the cured product by a solvent, the cured product of the adhesive composition of Example 2 was removed from the surface of the adherend by washing with ethylene glycol at 180°C. From this result, it can be understood that the adhesive composition of Example 2 has good removability of the cured product by a solvent.
[0118] Comparing Example 1 and Example 2, the adhesive composition of Example 2 containing polyrotaxane (d2) has a higher tensile shear adhesion strength at 25° C. than the adhesive composition of Example 1 containing polycaprolactone (d1), and has a lower tensile shear adhesion strength at 200° C. Therefore, from the comparison between Example 1 and Example 2, it can be understood that the adhesive composition containing polyrotaxane (d2) exhibits even better adhesion properties and ease of dismantling than the adhesive composition containing polycaprolactone (d1).
[0119] On the other hand, the adhesive composition of Comparative Example 1 did not contain either polycaprolactone (d1) or polyrotaxane (d2), and therefore had a lower tensile shear adhesive strength at 25°C and inferior adhesive properties compared to the adhesive compositions of Examples 1 and 2. Furthermore, the adhesive composition of Comparative Example 1 had a lower tensile shear strength after re-adhesion and inferior re-adhesion compared to the adhesive compositions of Examples 1 and 2.
[0120] The adhesive composition of Comparative Example 2 did not contain any of the transesterification catalyst (c), polycaprolactone (d1) and polyrotaxane (d2), and therefore had a lower tensile shear adhesive strength at 25°C and was inferior in adhesive properties compared to the adhesive compositions of Examples 1 and 2. The adhesive composition of Comparative Example 2 also had a lower tensile shear strength at 200°C and was inferior in ease of dismantling compared to the adhesive compositions of Examples 1 and 2. Furthermore, the adhesive composition of Comparative Example 2 could not be re-adhered after dismantling the bonded body, and did not have re-adhesive properties. Furthermore, in an evaluation of the removability of the cured product with a solvent, the cured product of the adhesive composition of Comparative Example 2 was not removed from the surface of the adherend by washing with ethylene glycol at 180°C, and remained on the surface of the adherend.
Claims
1. An epoxy resin (A), An acid anhydride curing agent (B); A transesterification catalyst (C); and (D) a polymer having an ester exchangeable group.
2. The adhesive composition according to claim 1 , wherein the adhesive composition comprises polycaprolactone (D1) as the polymer (D).
3. 2. The adhesive composition according to claim 1, wherein the adhesive composition comprises a polyrotaxane (D2) as the polymer (D), and the polyrotaxane (D2) has a cyclic molecule having a side chain including an ester group, and a linear molecule that is included in a ring of the cyclic molecule and has capping groups at both ends.
4. The adhesive composition according to claim 3 , wherein a side chain of the cyclic molecule contains a structural unit derived from polycaprolactone.
5. The adhesive composition according to any one of claims 1 to 4, wherein a test piece obtained by bonding an adherend made of aluminum with the adhesive composition has an adhesive property such that the tensile shear adhesive strength at 25°C is 20 MPa or more.
6. The adhesive composition according to any one of claims 1 to 4, having adhesive properties such that the tensile shear adhesive strength of the adhesive composition at 200°C is less than 10% of the tensile shear adhesive strength of the adhesive composition at 25°C.
7. 5. The adhesive composition according to claim 1, wherein a tensile shear bond strength test is conducted on a test piece obtained by bonding an adherend made of aluminum with the adhesive composition, and the test piece is broken to obtain two adherends, which are then re-adhered via a cured product of the adhesive composition, and the adhesive composition has adhesive properties such that the tensile shear bond strength at 25°C is 12 MPa or more.
8. A cured adhesive obtained by curing the adhesive composition according to any one of claims 1 to 4.
9. A first member; A second member; and a cured adhesive material interposed between the first member and the second member, A bonded structure, wherein the cured adhesive is the cured adhesive according to claim 8.
10. A method for manufacturing a bonded body including a first member, a second member, and an adhesive cured product interposed between the first member and the second member, comprising the steps of:
5. A method for producing a bonded body, comprising: interposing the adhesive composition according to claim 1 between the first member and the second member, and curing the adhesive composition in a state in which the adhesive composition is interposed.
11. A bonding method for bonding a first member and a second member using the adhesive composition according to any one of claims 1 to 4, comprising the steps of: contacting the first member and the second member with the adhesive composition; and and promoting a transesterification reaction between the epoxy resin (A) and the polymer (D).